VARIANTS AND ACTIVITY PHASES OF MANAGEMENT SYSTEM OF ENTERPRISES PRODUCT POLICY - Denis I. Lyndin (Статистика и экономика, 2016)
The purpose of the article is to study the peculiarities of development and the stages of activity of management system of product policy of enterprise. Author has established four variants of product policy on basis of classification signs, disclosed the contents and developed a sequence of designing, formation, support and optimization of management system of enterprise’s product policy.